140 Years of the Leçons sur l’histologie du système nerveux: the pioneering description of the nodes of Ranvier - Otto Jesus HERNANDEZ FUSTES; Cláudia Suemi Kamoi KAY; Paulo José LORENZONI; Renata Dal-Pra DUCCI; Jean-Gaël BARBARA; Lineu Cesar WERNECK; Rosana Herminia SCOLA (Arquivos de Neuro-Psiquiatria)
ABSTRACT This paper reviews aspects of the life and work of Professor Louis Ranvier 140 years after the publication of Leçons sur l’histologie du système nerveux, published in 1878, and shows the importance of the histological description of myelinated fibers of the nodes of Ranvier.